Thermal stress testing of a lotion containing a liposome-encapsulated lemongrass essential oil - Bagarinao, Cathrina (University of the Philippines, 2018)
For new drug products to be approved for commercialization, regulatory bodies such as the Food and Drug Administration, Require pharmaceutical manufacturers to prove claims of shelf-life, efficacy, and safety through a series of stability studies. Thermal stability of a drug product is one of the most important factors that drug developers investigate prior to releasing a drug into the market due to its great impact on the overall characteristics of a product. Thermal stability will ensure that the active pharmaceutical ingredient iin the product remains stable throughout the whole process of manufacture, storage, and use. Three groups of lotion formulations containing lemongrass essential oil as the active pharmaceutical ingredient were manufactured for the study. Group 1 contains free lemongrass essential oil while group 2 contains liposome-encapsulated lemongrass essentil oil. Group 3 contined the lotion base and served as the expriemnt blank. These were subjected to thermal stress at 60C and 75% relative humidity for 5 days. Samples were taken after 1, 3, and 5 days of exposure. The samples were then analyzed using Cary 5000 UV-Vis spectrometer. UV-Vis spectra of samples showed a prominent peak at 238.5 nm. This wavelength was used for quantitative calculations of the samples. A percent extracted range of 0.359+ 0.024 to 0.392 + 0.0071 was acquired for Group I formulation with a maximum decrease in concentration of 7.22%. The group 2 formulation, on the other hand, has a decrease of up to 54.61% by the end of the fifth day of exposure with an extracted range of o.503 on the first day up to 0.228 + 0.017 on the fifth day of the experiment. This encourages the development of a reformulated product which has an optimum concentration of liposome. The data lso suggest a first order degradation reaction which can be confirmed by subsequent thermal stability studies.